TA’LIMNI RIVOJLANTIRISHDA SUN’IY INTELLEKT VA RAQAMLI TRANSFORMATSIYA IMKONIYATLARI . (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article discusses the term AI (artificial intelligence) as it is increasingly used in our daily lives and its application is developing all over the world. Recently, artificial intelligence has been introduced into various industries and social infrastructures. For example, in the name of improving work methods, an increasing number of companies are implementing Robotic Process Automation (RPA) to automate work and increase productivity. RPA itself is not artificial intelligence, but it allows computers to take over simple tasks such as spreadsheet software and basic business systems, which are performed by humans in judgment, in other words, repetitive operations of a personal computer. In the future, we aim to automate the entire business by connecting them with handwritten character recognition, voice recognition, and response systems, which are applications of artificial intelligence.